Characterization and comparison of insulinoma tumor model and pancreatic damage caused by the tumor, and identification of possible markers - Karatuğ Kaçar, Ayşe; Bulutay, Pınar; Aylar, Dilara; Çelikten, Mert; Bolkent, Şehnaz (Springer Science and Business Media B.V., 2024)
Abstract: Insulinoma is a neuroendocrine tumor. It arises from the uncontrolled proliferation of pancreatic ? cells. In this study, we created an insulinoma tumor model in nude mice. INS-1 cells were injected in two different ways, subcutaneously (S.C.) or intraperitoneally (I.P.). Body weight, tumor weight, and size were measured. ELISA kits were used analyze to Glucose, insulin, and CA19-9 levels in serum, pancreas, and tumor tissues. KCNN4, KCNK1, GLUT2, IR, HSP70, HSF1, and HSP90 levels were analyzed by western blotting of membrane and/or cytosolic fractions of tumor and pancreas tissue. Tumor formation occurred in nude mice, but it did not occur in Wistar albino rats. The tumor has neuroendocrine cell morphology. Insulin and CA19-9 levels increased in pancreas tissue. In tumor tissue, KCNN4 levels were higher in both membrane and cytosolic fractions, while KCNK1 levels were lower in the membrane fraction of the S.C. group. HSP70 levels were also lower in the S.C. group. In pancreas tissue, KCNK1 levels were lower in the membrane fraction of the S.C. and I.P. groups. GLUT2 levels increased in both groups according to the control group, while IR levels decreased in the S.C. group compared to the control group. However, HSF1 levels increased in the I.P. group, while HSP90 decreased in the S.C. group in pancreatic tissues. The S.C. group is a more suitable insulinoma tumor model. KCNN4, KCNK1, and HSP70 proteins may be important biomarkers in the diagnosis and treatment of insulinoma.
Keywords: Biomarker; INS-1 Cell Line; Insulinoma; Pancreas; Subcutaneous Injection